2019
DOI: 10.1111/hsc.12872
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals’ experiences and perspectives on food insecurity and long‐term conditions: A qualitative investigation

Abstract: Estimates suggest that over 10% of the UK population are affected by food insecurity. International evidence indicates that food insecurity is a risk factor for many long-term health conditions, and can adversely affect people's ability to manage existing conditions. Food insecurity is thus not only a serious social concern but also a healthcare issue requiring the attention of UK health professionals. An exploratory qualitative study was undertaken to investigate the experiences and views of health profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…This is reflective of the findings of investigations of lived experiences of diabetes management in low income groups in Canada and the US (64,65). There is also emerging evidence that Scottish health care professionals are encountering patients who are also striving to manage diabetes through diet alone by decreasing their carbohydrate intake and increasing intakes of healthier alternative foods, but failing to sustain those behaviours (and achieving good glycaemic control) due to food costs and the stress of changes to household income (41).…”
Section: Discussionmentioning
confidence: 71%
“…This is reflective of the findings of investigations of lived experiences of diabetes management in low income groups in Canada and the US (64,65). There is also emerging evidence that Scottish health care professionals are encountering patients who are also striving to manage diabetes through diet alone by decreasing their carbohydrate intake and increasing intakes of healthier alternative foods, but failing to sustain those behaviours (and achieving good glycaemic control) due to food costs and the stress of changes to household income (41).…”
Section: Discussionmentioning
confidence: 71%
“…This is re ective of the ndings of investigations of lived experiences of diabetes management in low income groups in Canada and the US [72,73]. There is also emerging evidence that Scottish health care professionals are encountering patients who are also striving to manage diabetes through diet alone by decreasing their carbohydrate intake and increasing intakes of healthier alternative foods, but failing to sustain those behaviours (and achieving good glycaemic control) due to food costs and the stress of changes to household income [49].…”
Section: Discussionmentioning
confidence: 83%
“…Those include on the patient side, feelings of stigma and powerlessness, and on the health care professional side, professional attitudes, con dence, training, and, available health care contact time [87]. There is also some emerging evidence that health care professionals are not only reluctant to raise the issue of nancial challenges with patients but admit to having trouble recognising if someone was struggling to put food on the table [49,88]. Social distance between health care professionals and patients is also theorised as a barrier to effective and empathetic interaction [89][90][91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of attention is in contrast to other high-income countries where poverty and food insecurity, and long-term condition prevalence are similarly high [20,22,24,[41][42][43][44][45][46]. A recent study of Scottish-based health care professionals, by the lead author, found that most believed that some of their patients were affected by food insecurity and that it was impacting their ability to manage their health condition(s) [47]. There were particular concerns about medication adherence and side effects, diet dependant conditions and mental health.…”
Section: Introductionmentioning
confidence: 99%